Negative and positive feedback from a supernova remnant with SHREC: a detailed study of the shocked gas in IC443. Issue 1 (12th January 2022) - Cosentino, G; Jiménez-Serra, I; Tan, J C; Henshaw, J D; Barnes, A T; Law, C-Y; Zeng, S; Fontani, F; Caselli, P; Viti, S; Zahorecz, S; Rico-Villas, F; et al.
ABSTRACT: Supernova remnants (SNRs) contribute to regulate the star formation efficiency and evolution of galaxies. As they expand into the interstellar medium (ISM), they transfer vast amounts of energy and momentum that displace, compress, and heat the surrounding material. Despite the extensive work in galaxy evolution models, it remains to be observationally validated to what extent the molecular ISM is affected by the interaction with SNRs. We use the first results of the ESO–ARO Public Spectroscopic Survey SHREC to investigate the shock interaction between the SNR IC443 and the nearby molecular clump G. We use high-sensitivity SiO(2-1) and H 13 CO + (1-0) maps obtained by SHREC together with SiO(1-0) observations obtained with the 40-m telescope at the Yebes Observatory. We find that the bulk of the SiO emission is arising from the ongoing shock interaction between IC443 and clump G. The shocked gas shows a well-ordered kinematic structure, with velocities blue-shifted with respect to the central velocity of the SNR, similar to what observed towards other SNR–cloud interaction sites. The shock compression enhances the molecular gas density, n(H2 ), up to >10 5 cm −3, a factor of >10 higher than the ambient gas density and similar to values required to ignite star formation. Finally, we estimate that up to 50 per cent of the momentum injected by IC443 is transferred to the interacting molecular material. Therefore, the molecular ISM may represent an important momentum carrier in sites of SNR–cloud interactions.